(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the formation of special competencies of future technological education teachers based on an integrative approach as a pedagogical problem. The purpose of the future technological education teacher to be able to apply the knowledge acquired in his specialty and to have professional qualities is shown.